Numerical optimization of gas cooler geometry in transcritical refrigeration cycles - URKUT, AHMET FURKAN; ÖZDEMİR, MEHMED RAFET (My University, 2023)
Traditional halocarbon – based refrigerants tend to considerably increase global warming and ozone depletion factors. Therefore, CO2 is fast becoming a key instrument as a natural refrigerant which was widely applied and attracted the consideration of the research community. The gas cooler is a critical component in the CO2 transcritical refrigeration system and plays a major role in the performance due to the determination of operating pressure consequently power consumption. In this research, the performance characteristics of a CO2 gas cooler having wavy fin geometry, which is currently employed in industries including air conditioning, automotive and aviation, was determined experimentally in a calorimetric test room. The experimental results was used as benchmark data to validate the three – dimensional numerical model. Laminar model and realizable k - ɛ turbulent model were employed for analyses. Moreover, the second order upwind scheme was considered to discretize momentum and energy equations. Accordingly, a multi-objective optimization process has been performed employing Response Surface Method (RSM) to determine the optimum wavy fin geometry in CO2 transcritical refrigeration system. Four geometrical parameters namely longitudinal pitch, half transverse pitch, tube outer diameter, and fin pitch of the gas cooler were optimized. According to results, the new optimized CO2 gas cooler exhibited lesser pressure drop and higher heat transfer capacity in comparison with the tested gas cooler geometry used in the industry. It was appeared that the overall heat transfer coefficient enhancement is between 5.4 – 12.2 % while pressure drop decreases about 175.08 – 188.58 % for three different inlet velocities

Geleneksel halokarbon bazlı soğutucu akışkanlar, küresel ısınmayı ve ozon tabakasını inceltme faktörlerini önemli ölçüde artırma eğilimindedir. Bu nedenle, araştırma topluluğunun dikkatini çeken ve hızla yaygın olarak uygulanan doğal bir soğutucu olarak CO2 önemli bir araç haline gelmektedir. Gaz soğutucu, CO2 transkritik soğutma sisteminde önemli bir bileşendir ve çalışma basıncının ve dolayısıyla güç tüketiminin belirlenmesi nedeniyle performansta önemli bir rol oynar. Bu araştırmada, günümüzde iklimlendirme, otomotiv ve havacılık gibi sektörlerde kullanılan dalgalı kanatçık geometrisine sahip bir CO2 gaz soğutucunun performans özellikleri kalorimetrik bir test odasında deneysel olarak belirlenmiştir. Deneysel sonuçlar, üç boyutlu sayısal modeli doğrulamak için ölçüt olarak kullanılmıştır. Analizler için laminer model ve realizable k - ɛ türbülanslı model kullanılmıştır. Ayrıca momentum ve enerji denklemlerini ayrıklaştırmak için second order upwind şeması kullanılmıştır. Buna göre, CO2 transkritik soğutma sisteminde optimum dalgalı kanatçık geometrisini belirlemek için Yanıt Yüzey Yöntemi (RSM) kullanılarak çok amaçlı bir optimizasyon işlemi gerçekleştirilmiştir. Gaz soğutucunun boyuna hatvesi, yarım enine hatvesi, boru dış çapı ve kanatçık hatvesi olmak üzere dört geometrik parametre optimize edilmiştir. Sonuçlara göre, yeni optimize edilmiş CO2 gaz soğutucusunun, endüstride kullanılan test edilmiş gaz soğutucu geometrisine kıyasla daha az basınç düşüşü ve daha yüksek ısı transfer kapasitesi sergilediği görülmüştür. Üç farklı giriş hızı için ortalama ısı transfer katsayısı iyileşmesinin %5,4 – 12,2 arasında olduğu, basınç düşüşünün ise % 175,08 – 188,58 oranında azaldığı görülmüştür.
Transkritik soğutma çevrimlerinde gaz soğutucu geometrisinin sayısal optimizasyonu
Keywords: natural refrigerants; heat transfer coefficient; gas cooler; optimization; wavy fin; doğal soğutucular; ısı transferi katsayısı; gaz soğutucu; optimizasyon; dalgalı kanatçık